Investigation of Polycaprolactone/Carboxymethyl Cellulose Scaffolds by Mechanical and Thermal Analysis - Sriputtha, N.; Wiwatwongwana, F.; Promma, N. (Engineering, Technology & Applied Science Research, 2022)
The objective of this work was to learn more about three-dimensional porous scaffolds made from biomaterial based on polycaprolactone (PCL) containing different amounts of carboxymethyl cellulose (CMC) nanoparticles. Composite material samples containing 0, 2, 6.5, 11, 15.5, and 20% w/w of CMC and PCL/CMC scaffolds were prepared with the use of the salt particle leached technique. The mechanical properties were evaluated with the compressive strength analysis method. The studied temperature range started at very low temperatures and ended at crosslinking temperatures. It was evaluated using the thermal analysis methods of Differential Scanning Calorimetry (DSC) in the range 0ºC-200ºC. The results revealed that the compressive modulus of blended PCL/CMC scaffold was higher than the one of pure PCL scaffold (582.2±106.2 kPa for pure PCL scaffold and 612.2±296 kPa for blended scaffold which contained 20% of CMC). For DSC analysis, in addition to the 15.5% w/w CMC PCL/CMC composite scaffold, other proportions of composite materials showed a decrease in crystallization temperature. The crystallinity of PCL-20% CMC was higher than that of PCL scaffolds.